Penerapan Hybrid Learning dalam Pembelajaran Pendidikan Agama Islam Kontekstual - Darul lailatul Qomariyah (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2021)
The study is aimed to know how to implement Hybrid Learning in contextual Islamic studies learning in high school. Hybrid Learning means the measurable combination between in-person and distance learning. Contextual Islamic studies learning aims to facilitate the students to actualize and internalize the values contained in Islamic studies by learning experiences during the learning process. This study offers some steps to do to implement Hybrid Learning in contextual Islamic studies learning. The implementation of Hybrid Learning in contextual Islamic studies needs to be tested, observed, and evaluated to make it successful at the future.